An RNA map predicting Nova-dependent splicing regulation - Ule, Jernej; Stefani, Giovanni; Mele, Aldo; Ruggiu, Matteo; Wang, Xuning; Taneri, Bahar; Gaasterland, Terry M. (Nature Publishing Group, 2006)
Nova proteins are a neuron-specific alternative splicing factors. We have combined bioinformatics, biochemistry and genetics to derive an RNA map describing the rules by which Nova proteins regulate alternative splicing. This map revealed that the position of Nova binding sites (YCAY clusters) in a pre-messenger RNA determines the outcome of splicing. The map correctly predicted Nova's effect to inhibit or enhance exon inclusion, which led us to examine the relationship between the map and Nova's mechanism of action. Nova binding to an exonic YCAY cluster changed the protein complexes assembled on pre-mRNA, blocking U1 snRNP (small nuclear ribonucleoprotein) binding and exon inclusion, whereas Nova binding to an intronic YCAY cluster enhanced spliceosome assembly and exon inclusion. Assays of splicing intermediates of Nova-regulated transcripts in mouse brain revealed that Nova preferentially regulates removal of introns harbouring (or closest to) YCAY clusters. These results define a genome-wide map relating the position of a cis-acting element to its regulation by an RNA binding protein, namely that Nova binding to YCAY clusters results in a local and asymmetric action to regulate spliceosome assembly and alternative splicing in neurons. ©2006 Nature Publishing Group.
Keywords: Binding energy; Bioassay; Brain; Neurology; RNA; Neuron-specific; Nova binding sites; RNA map; YCAY cluster; Proteins; adenine; cis acting element; cytosine; messenger RNA precursor; nova protein; pyrimidine; regulator protein; RNA binding protein; small nuclear ribonucleoprotein; u1 small nuclear ribonucleoprotein; bioassay; biochemistry; bioinformatics; genetic analysis; mapping method; molecular analysis; alternative RNA splicing; animal tissue; article; binding site; brain; complex formation; controlled study; embryo; exon; mouse; nerve cell; nonhuman; prediction; priority journal; protein assembly; protein binding; protein expression; protein function; reverse transcription polymerase chain reaction; rna map; spliceosome